2011
DOI: 10.1136/thoraxjnl-2011-200329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of late preterm birth on longitudinal lung spirometry in school age children and adolescents

Abstract: Background Rates of preterm birth have increased in most industrialised countries but data on later lung function of late preterm births are limited. A study was undertaken to compare lung function at 8e9 and 14e17 years in children born late preterm (33e34 and 35e36 weeks gestation) with children of similar age born at term ($37 weeks gestation). Children born at 25e32 weeks gestation were also compared with children born at term. Methods All births from the Avon Longitudinal Study of Parents and Children (n¼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
132
4
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(149 citation statements)
references
References 29 publications
9
132
4
4
Order By: Relevance
“…Although reports of lung function at school age and adolescence are sparse in subjects born moderate to late preterm, a study by Kotecha et al 12 reported similar results as in our study, with significantly lower lung function at 8 to 9 years of age for children born after 33 to 34 weeks of gestation, compared with term control subjects. However, they found no significant negative effects among those born after 35 to 36 weeks of gestation.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Although reports of lung function at school age and adolescence are sparse in subjects born moderate to late preterm, a study by Kotecha et al 12 reported similar results as in our study, with significantly lower lung function at 8 to 9 years of age for children born after 33 to 34 weeks of gestation, compared with term control subjects. However, they found no significant negative effects among those born after 35 to 36 weeks of gestation.…”
Section: Discussionsupporting
confidence: 79%
“…Quality control was performed at the time of examination by visual inspection of the waveforms. Given that coherence, which is a measure of testing reliability, was >0.80 at 10 Hz, the mean value of resistance at 5 Hz (R 5 ), resistance at 20 Hz (R 20 ), frequency dependence of resistance (ie, R [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and reactance area (AX) were used for analysis. AX may boost the assessed response inappropriately compared with the R 5-20 response because it multiplies 2 partly independent reactions of the airways.…”
Section: Measurements Of Lung Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from six infants born between 36 and 37 weeks gestation were however included as there is no evidence of changes in subsequent lung function at such gestations. 35 Ideally, we would have studied a multi-ethnic group of children to ascertain the potential impact of ethnic origin and allow application of these reference equations to all infants presenting for lung function tests. This was beyond the scope of the present study, especially as many of the infants had been recruited as controls when studying infants with Cystic Fibrosis, a disease predominantly affecting those of White European descent.…”
Section: Populationmentioning
confidence: 99%
“…The two main factors that constitute impedance are resistance (R) and reactance (X). It is measured between certain frequencies (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). When R and X are measured at 5 Hz, they are named R5 and X5.…”
Section: Impulse Oscillometermentioning
confidence: 99%